A High-Efficiency Silicon-Carbide Bidirectional Industrial Switched Reluctance Motor Drive - Francisco Juarez-Leon; Berker Bilgin (IEEE Access)
Switched reluctance motors (SRMs), known for their simple construction, high efficiency, and robustness, are increasingly being adopted across various applications. In an industrial setting, these motors offer a promising alternative to traditional induction motors (IMs), particularly due to their lower sensitivity to temperature and ability to perform reliably in harsh environments. While commercially available variable frequency drives (VFDs) are readily accessible for IMs, the same is not true for SRMs, limiting their broader adoption in the industry. This paper presents the design and implementation of a high-efficiency, integrated, bidirectional drive for an SRM for industrial applications. An analysis of the current SRM market, along with a review of related research, has been conducted. Based on this analysis, existing gaps in SRM drive solutions have been identified, and the design requirements for the proposed drive have been defined. Subsequently, a 10 kW silicon-carbide (SiC)-based converter topology is designed, developed, and experimentally validated. The proposed converter achieves a peak efficiency of 97.03% at the power factor correction (PFC) stage and 98.90% at the motor drive stage under nominal power conditions.